1970
DOI: 10.3126/hjs.v1i2.205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gibberellic acid on reserve food mobilization of maize (Zea mays L. var Arun-2) endosperm during germination

Abstract: In the first 24 hrs of germination, the dry matter of the growth axis decreased in the control while in 1 mg/l GA3 solution it increased and in 10 mg/l and 100 mg/l the amount remained the same. Exogenous GA3 overcomes the dry matter loss in the growth axis during the initial stage and results in an increase in the amount of dry matter. GA3 application probably mobilized more soluble sugar to the growth axis, which results in an increase in the amount of soluble sugar in the growth axis as compared to caryopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Increased hydrolysis and biosynthesis under the influence of 3C and 4.5C potencies (Figure 1) could be connected to a better substance conversion from the seed rest to the root and shoot. All genotypes showed higher biosynthesis with the highest values achieved for L3, with an increase in hydrolysis to 27% and in biosynthesis to 40% when treated by 4.5C, similarly to Subedi and Bhattarai 30 (when seed was treated with different growth regulators). The 4.5C affected biosynthesis (which is susceptible to injuries) and has a positive impact on the germination of susceptible genotypes, such as L3.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Increased hydrolysis and biosynthesis under the influence of 3C and 4.5C potencies (Figure 1) could be connected to a better substance conversion from the seed rest to the root and shoot. All genotypes showed higher biosynthesis with the highest values achieved for L3, with an increase in hydrolysis to 27% and in biosynthesis to 40% when treated by 4.5C, similarly to Subedi and Bhattarai 30 (when seed was treated with different growth regulators). The 4.5C affected biosynthesis (which is susceptible to injuries) and has a positive impact on the germination of susceptible genotypes, such as L3.…”
Section: Discussionmentioning
confidence: 71%
“…The sugary lines had lower hydrolysis and biosynthesis in the controls, indicating their poorer ability to germinate and produce strong plants with a high FS (Tables 1 and 2). Subedi and Bhattarai 30 observed that maize germination correlates directly with the mobilization of the endosperm reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is last observation is in perfect agreement with the work of [51] on saffron. us, the results of previous research have shown that exogenous spraying of GA 3 in some bulbous plants inhibited the growth of lateral buds of mother bulbs, which gave rise to large replacement corms and, therefore, a better flowering yield [52,53]. However, [54,55] found that gibberellic acid had no effect on the number and weight of ).…”
Section: Weight Number and Diameter Of Cormsmentioning
confidence: 99%
“…Presence of high concentrations of various metals in soil either essential or non-essential causes a significant perturbation in carbohydrates (Jha and Dubey, 2005). As a result of this direct influence on activity of metabolic enzymes of germinating seeds, the level of vital biomolecules including sugars, proteins, amino acids and nucleotides is altered (Subedi and Bhattarai, 2003). Another enzyme, protease is thought to participate in various physiological as well as metabolic process of plants related to protein turnover.…”
Section: Discussionmentioning
confidence: 99%